Evidence of defect-mediated magnetic coupling on hydrogenated Co-doped ZnO - Godoy, M. P. F. de; Mesquita, A.; Avansi, W.; Neves, P. P.; Chitta, V. A.; Ferraz, W. B.; Boselli, M. A.; Sabioni, A. C. S.; Carvalho, H. B. de (Elsevier, 2013)
Hydrogenated bulk Zn1-xCoxO samples were synthesized via standard solid-state reaction route with Co molar concentrations up to 15 at.%. Magnetic characterization demonstrates a room temperature ferromagnetic behavior associated to a paramagnetic Curie-Weiss component. Detailed microstructural analysis was carried out to exclude the presence of extrinsic sources of ferromagnetism. The magnetization increases linearly as a function of Co concentration. Hall measurements reveal an insulating character for the whole set of samples. In this context, the defect mediated magnetic coupling between the Co atoms under the scope of the bound magnetic polarons model is used to interpret the observed room temperature ferromagnetism. © 2012 Elsevier B.V. All rights reserved.
Keywords: Magnetic measurements; Magnetically ordered materials; Oxide materials; Scanning tunnelling microscopy; Solid state reactions; STM, Synchrotron radiation; X-ray diffraction; Bound magnetic polarons; CO concentrations; Co-doped ZnO; Ferromagnetic behaviors; Hall measurements; Magnetic characterization; Magnetically ordered material; Microstructural analysis; Molar concentration; Room temperature; Room temperature ferromagnetism; Defects; Ferromagnetism; Hydrogenation; Magnetic couplings; Magnetic variables measurement; Paramagnetism; Scanning tunneling microscopy; X ray diffraction; Characterization